THE TRANSPORTABILITY OF WESTERN PSYCHOLOGY - David L Krantz (Buletin Psikologi, 1993)
During the six months I was a Fulbright lecturer in Indonesia I became acutely aware that some topics in psychology travelled well while others did not. When I taught methodology or talkde about laboratory, "hard" research findings, my student and I found the material relevant to the Indonesia context.